The influence of the independent board of commissioners, gender diversity, and institutional ownership on carbon emissions disclosure - Gunawan Barbara; Megandari Meyda A. (SHS Web of Conferences)
This research examines the influence of the Independent Board of Commissioners, Gender Diversity, and Institutional Ownership on Carbon Emissions Disclosure. The objects of this research are energy, transportation, and logistics sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. In this research, the samples from 48 companies were selected using purposive sampling. The analysis tool used is SPSS ver. 22. This research found that independent boards of commissioners and gender diversity did not influence carbon emissions disclosure, while institutional ownership positively affected carbon emissions disclosure.